The Right of Inquiry of the House of Representatives Against the Corruption Eradication Commission in Indonesia - Dirsa Deandaru (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The supervisory function of the House of Representatives (Dewan Perwakilan Rakyat/DPR) serves as an instrument of checks and balances over the executive branch, including through the right of inquiry (hak angket) to investigate the implementation of laws and government policies. Problems arise when this right is directed at the Corruption Eradication Commission (Komisi Pemberantasan Tindak Pidana Korupsi/KPK), which, although situated within the executive sphere, was designed as an independent state institution to safeguard law enforcement from political interference. This article analyzes the constitutional position of the KPK and the limits of applying the DPR's right of inquiry to it. The analysis shows that the KPK constitutes a state auxiliary institution with functional independence; accordingly, pro justitia measures such as investigation, inquiry, and prosecution fall outside the scope of political oversight. Therefore, the use of the right of inquiry against the KPK must be proportionally confined to administrative policy and institutional governance so as not to undermine the independence of anti-corruption law enforcement.